(untitled) (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
This study looked at the students’ satisfaction with the food offered at the canteen. A school utilizes a canteen to meet the food and nutritional needs of its students in order for them to have the energy to accomplish the tasks that they would do for the day. The survey revealed that the majority of the respondents are female between the ages of 19 and 21. Among the 100 respondents, 16% are in the 4th year, 22% are 3rd year, 36% are 2nd year and 26% are 1st year. The respondents are equally divided into 50% BSHM and 50% BSTM students. The assessment of student satisfaction in terms of food preference, food quality, food prices, food, and facilities and equipment has a positive result, or as satisfied with a weighted mean of 2.74. The assessment of student satisfaction in terms of tangibility, reliability, responsiveness, assurance, and empathy with a weighted mean of 2.75. It indicates that through participation and collaboration of the institution, the school canteen improves the food that they offer to the customers. Students will benefit from its results with the help of the school administration by improving and maintaining the order of the school canteen. The students’ satisfaction with food offered at the canteen in BCP assessment can be identified and resolved using various methods and approaches.